Synthesis of Macroheterocycles and Complexation With Palladium(II) and Silver(I) - SALHI, RAMDANE (Asian Journal of Chemistry, 2010)
In present studies, the synthesis of 2-chloroquinoline-3-carbaldehyde derivatives from acetanilide as starting materials, to prepare macroheterocycles and their reaction with heavy metals to test the selectivity of extracting them from their mixtures in the industrial residues are reported.